Eye Tracking Technology: A Potentially Potent Tool for Education Research - Yang, Yaodong (Science Insights Education Frontiers, 2025)
For human beings, the eye is the most vital tool for observing the world and obtaining information from the environment. At the same time, it is constantly revealing the mental state and activity of the individual via the direction, duration, and trajectory of its gaze, as well as its saccade frequency and the contraction and dilation of its pupil. Eye-tracking technology is to collect eye movement data using sensor technology and computer image processing (Sun et al., 2018). Typically, the eye tracker records eye movements and identifies gaze points by projecting an infrared or near-infrared light to the eye (Da Silva Soares et al., 2023). Early eye-tracking equipment was bulky and costly; nevertheless, with the advancement of technology, today’s eye-tracking devices have become more portable, cost-effective, precise, and as a result, increasingly popular in various fields, particularly in science research.